Comment on Gomez et. al. "Response to article by Wasserman et. al. (2018) 'Modelling the sustained use of the 13-valent pneumococcal conjugate vaccine compared to switching to the 10-valent vaccine in Mexico'" - Matt Wasserman; Maria Gabriela Palacios; Ana Gabriela Grajales; Michele Wilson; Cheryl McDade; Raymond Farkouh (Taylor & Francis Group, 2019)
In a recent Letter, Gomez et. al. provided a critique of our original analysis estimating the clinical and economic impact of switching from the 13-valent (PCV13) to the 10-valent (PCV10) pneumococcal conjugate vaccine in Mexico. This comment addresses Gomez et. al.'s comments with additional information and clarifies potential misinterpretations.